Ideology in Nijo Text on the Speech Community of Lio Flores: Ecolinguistic Perspective - Genua, Veronika; Simpen, I Wayan; Mbete, Aron Meko; Putra Yadnya, Ida Bagus (e-Journal of Linguistics; Vol 12 No 1 (2018): eJL-January, 2018)
The study about ideology of nijo text in traditional medication is sociolinguistic study, in particular ecolinguistic field. Ecolinguistics discusses the interaction, interrelation, and interdependence between humans and the natural environment. In addition, there are also three dimensions, namely ideological, sociological, and biological dimensions relating to the exploitation of the environment for health through traditional medication on Lio Flores speech community. The problems of this study include how  are the ideology, and meanings in the content of nijo text on Lio Flores speech community. The objectives of this study are to describes the ideology and meanings embodied in Lio Flores speech community. The result of this study describe that there is an ideology of belief in nijo text. Additionally, there are also meanings and values in the text, such as stylistic, affective, religious, reflective, and social meanings. In addition, the values imply pursuance, defenselessness, and harmony. An example of defenselessness seen in data is lele dala 'follow the stars' that means always defenseless and surrender to the power and the ancestors as the guardian of life. Keywords : nijo, ideology, belief, and health